Expression and function of OXE receptor, an eicosanoid receptor, in steroidogenic cells - Cooke, Mariana (2013)
Hormonal regulation of steroidogenesis involves arachidonic acid (AA) metabolism through the 5-lipoxygenase pathway. One of the products, 5-hydroperoxy-eicosatetraenoic acid (5-HpETE), acts as a modulator of the activity of the steroidogenic acute regulatory (StAR) protein promoter. Besides, an oxoeicosanoid receptor of the leukotriene receptor family named OXE-R is a membrane protein with high affinity and response to 5-HpETE, among other AA derivatives. The aim of our work was to elucidate whether this receptor may be involved in steroidogenesis. RT-PCR and western blot analysis demonstrated the presence of the mRNA and protein of the receptor in human H295R adrenocortical cells. The treatment of H295R or MA-10 cells (murine Leydig cell line) with 8Br-cAMP together with docosahexaenoic acid (DHA, an antagonist of the receptor) partially reduced StAR induction and steroidogenesis. On the contrary, 5-oxo-ETE -the prototypical agonist, with higher affinity and potency on the receptor- increased cAMP-dependent steroid production, StAR mRNA and protein levels. These results lead us to conclude that AA might modulate StAR induction and steroidogenesis, at least in part, through 5-HpETE production and activation of a membrane receptor, such as the OXE-R